Die Berliner Lederhandschrift: À propos Berlin P3029, I, 17–19 - Graefe, Erhart (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
The three lines I, 17–19 of Berlin P3029 are reconsidered, e. g. the value and meaning of two groups of hieratic signs whose interpretation to date is controversial. Furthermore, it is argued that this text of Middle Kingdom origin does not give any precise hint which kind of monument ( ḥw.t ) Sesostris I wanted to build in Heliopolis besides a canal or lake.